Prevalence of Multi-Resistant Microorganisms and Antibiotic Stewardship among Hospitalized Patients Living in Residential Care Homes in Spain: A Cross-Sectional Study - Mario Rivera-Izquierdo; Alberto Benavente-Fernández; Jairo López-Gómez; Antonio Jesús Láinez-; Marta Rodríguez-Camacho; María del Carmen Valero-Ubierna; Luis Miguel Martín-delosReyes; Eladio Jiménez-Mejías; Elena Moreno-Roldán; Pablo Lardelli-Claret; Virginia Martínez-Ruiz (MDPI AG, 2020)
Antimicrobial resistance is a growing global health problem. Patients living in care homes are a vulnerable high-risk population colonized by multidrug-resistant organisms (MDRO). We identified a case series of 116 residents of care homes from a cohort of 540 consecutive patients admitted to the internal medicine service of our hospital. We performed early diagnostic tests of MDRO through anal exudates in our sample. The prevalence of MDRO colonization was 34.5% of residents and 70% of them had not been previously identified in the clinical records. Previous hospitalizations and in-hospital antibiotic administration were significantly associated with the presence of MDRO. Our results emphasize the need to consider care homes in the planning of regional and national infection control measures and for implementing surveillance systems that monitor the spread of antimicrobial resistance in Spain. Systematic early testing upon admission to hospital services with a high prevalence of patients with MDRO colonization (e.g., internal medicine) could contribute to the adoption of adequate prevention measures. Specific educational programs for care home staff should also be implemented to address this increasing problem.